2018
DOI: 10.17305/bjbms.2017.2201
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia for patients with mucopolysaccharidoses: Comprehensive review of the literature with emphasis on airway management

Abstract: Mucopolysaccharidoses (MPS) are rare, inherited, lysosomal storage diseases that cause accumulation of glycosaminoglycans, resulting in anatomic abnormalities and organ dysfunction that can increase the risk of anesthesia complications. We conducted a systematic review of the literature in order to describe the anesthetic management and perioperative outcomes in patients with MPS. We reviewed English-language literature search using an OVID-based search strategy of the following databases: 1) PubMed (1946-pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 41 publications
(69 reference statements)
1
39
1
6
Order By: Relevance
“…Mucopolysaccharidosis (MPS) type II, also known as Hunter syndrome, is a rare X‐lined recessive disease caused by deficiencies of lysosomal enzymes that lead to the accumulation of glycosaminoglycans (GAGs) . Accumulated GAGs in the upper airway can lead to severe airway obstruction due to macroglossia, tonsil and adenoid hypertrophy, vocal cord enlargement, supraglottic narrowing, and tracheomalacia . In particular, MPS II patients have a higher incidence of difficult airway than other types of MPS patients .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucopolysaccharidosis (MPS) type II, also known as Hunter syndrome, is a rare X‐lined recessive disease caused by deficiencies of lysosomal enzymes that lead to the accumulation of glycosaminoglycans (GAGs) . Accumulated GAGs in the upper airway can lead to severe airway obstruction due to macroglossia, tonsil and adenoid hypertrophy, vocal cord enlargement, supraglottic narrowing, and tracheomalacia . In particular, MPS II patients have a higher incidence of difficult airway than other types of MPS patients .…”
Section: Introductionmentioning
confidence: 99%
“…1 Accumulated GAGs in the upper airway can lead to severe airway obstruction due to macroglossia, tonsil and adenoid hypertrophy, vocal cord enlargement, supraglottic narrowing, and tracheomalacia. 2,3 In particular, MPS II patients have a higher incidence of difficult airway than other types of MPS patients. 4,5 Therefore, it can be challenging to achieve the desired level of sedation while maintaining a patent airway and ensuring ventilation during deep sedation of such patients.…”
Section: Introductionmentioning
confidence: 99%
“…As there is a phenotypic variety, the anesthesiologist may use one or more devices to obtain the optimal ventilation (Figure ) …”
Section: Mucopolysaccharidosesmentioning
confidence: 99%
“…Anesthetic airway management in a series of 49 patients (Mayo Clinic) with MPS. Reproduced with permission Clark et al…”
Section: Mucopolysaccharidosesmentioning
confidence: 99%
“…Therefore, airway‐related anesthetic complications in patients with MPS I are also a part of pediatric anesthesia. Clark et al found that the overall incidence of difficult tracheal intubation in a case series of various types of MPS ranged from 28% to 44%. Regional anesthesia seems to be a logical choice for these patients.…”
Section: Introductionmentioning
confidence: 99%